Optimization of the Acquisition Time and Injected Dose of 18F-Fluorodeoxyglucose Based on Patient Specifications for High-Sensitive Positron Emission Tomography/Computed Tomography Scanner - Al-Fatlawi, Murtadha; Pak, Farideh; Farzanefar, Saeed; Salehi, Yalda; Monsef, Abbas; Sheikhzadeh, Peyman (World Journal of Nuclear Medicine, 2023)
Background This study was aimed to optimize the fluorodeoxyglucose (FDG)-administered dose and scan time based on patient specifications using a highly sensitive five-ring bismuth germanium oxide (BGO)-based positron emission tomography/computed tomography (PET/CT) scanner (Discovery IQ).Methods We retrospectively analyzed 101 whole-body 18F-FDG PET/CT images. Patient data were reconstructed using ordered subset expectation maximization with resolution recovery algorithms (OSEM + SharpIR). Signal-to-noise ratio (SNR) was calculated for each patient, standardized to SNRnorm, and plotted against three body index parameters (weight, body mass index, and lean body mass). Two professional physicians blindly examined image quality at different patient time per bed positions to determine the minimum acceptable quality. To select images of acceptable quality, the noise index parameter was also measured. A new dose-time product (DTP) was established for each patient, and a predicted injected dose was assumed.Results We found an almost linear association between patient weight and normalized SNR, and patient weight had the highest R2 in the fitting. The redesigned DTP can reduce results by approximately 74 and 38% compared with ordinary DTP for 80- and 160-s scan durations. The new dose regimen formula was found to be DTP = c/t × m1.24, where m is the patient weight, t is the scan time per bed position, and c is 1.8 and 4.3 for acceptable and higher confidence states, respectively, in Discovery IQ PET/CT.Conclusion Patient weight is the best clinical parameter for the implementation of 18F-FDG PET/CT image quality assessment. A new dose-time regimen based on body weight was proposed for use in highly sensitive five-ring BGO PET-CT scanners to significantly reduce the injection dose and scan times while maintaining sufficient image quality for diagnosis.
Keywords: dose optimization; BGO-based positron-emission tomography; dependency; reconstruction algorithm